Black-hearted Sellers in the Skincare Industry: Their Activities and Prevention Strategies - Pua, Sin Yi; Chew, Boon Cheong (Journal of Technology Management and Business, 2023)
While online purchases have increased substantially since the pandemic, the cases of “black-hearted” sellers taking advantage of their buyers using unethical activities or marketing tactics are increasing as well, especially in the skincare industry. If this continues, it will subsequently result in the online platform to become ‘untrustable’ among the skincare buyers. Hence, this paper aims to examine the activities of black-hearted sellers and suggest solutions that could prevent them from conducting their businesses. Using semi-structured interviews conducted with 20 experienced official skin care sellers, this paper found that the activities generated by the black-hearted sellers are counterfeiting, parallel imports, misleading information, reselling without authorisation, and identity theft. Also, several strategies that can prevent these activities are quality strategy, adjusting price strategies, technology strategies, enforcement strategies, supply chain structure, and marketing communication strategies.